FACTORS AFFECTING THE ABILITY OF FISHERIES COMPANIES THAT ARE REGISTERED IN INDONESIA STOCK EXCHANGE (IDX) - mansur, Syahrul (Global Science Education Journal, 2019)
The purpose of this study is to obtain profits or profits for a company that can be used for survival. Getting profits or profits and the size of profits is often a measure of the success of a management. This is supported by management's ability to see possibilities and opportunities in the future. Management is required to produce decisions that support the achievement of company goals and accelerate the development of the company.